KEBIASAAN BELAJAR SISWA PADA MATA PELAJARAN AKUNTANSI DASAR KELAS X SMK NEGERI 7 PONTIANAK - Aprillina Aprillina; Achmadi Achmadi; Rum Rosyid (Universitas Tanjungpura, 2021)
AbstractThis study aims to determine the study habits of students in basic accounting subjects in class X at SMK Negeri 7 Pontianak. This study focuses more on the learning habits carried out by students, especially the study habits of students at home in basic accounting subjects. The research method used is descriptive method with qualitative research type. Sources of data in this study were students of class X Accounting A SMK Negeri 7 Pontianak with a sample of 5 students and their parents to conduct direct interviews, researchers conducted interviews by directly visiting each student's residence with different days, dates and times. The results showed that 1). providing a place to study, facilities and learning equipment is categorized as quite good, namely 3 out of 5 respondents have met this indicator. 2). regulating the study time is categorized as good, namely 4 out of 5 respondents have met this indicator. 3). repeating the lesson material is categorized as good, namely 4 out of 5 respondents have met this indicator 4). getting rid of those that interfere with concentration is categorized as not good, namely only 2 out of 5 respondents who meet this indicator.Keywords: At home, Basic accounting, Student study habits,